Persepsi Masyarakat terhadap Dampak Bau dan Kebersihan Lingkungan Akibat Limbah Peternakan Sapi Bali - Marhayani, Marhayani; Yunita, Elsa (Fakultas Peternakan Universitas Madako Tolitoli, 2024)
This study aims to determine the public perception of the impact of Bali cattle farm waste, focusing on aspects of odor and environmental cleanliness. The research employed a quantitative descriptive method with a field survey approach, involving 50 respondents selected through simple random sampling. Data were collected using questionnaires and direct interviews, then analyzed using a five-point Likert scale to assess the level of community disturbance caused by livestock waste. The results showed that the community experienced a high level of disturbance from the presence of Bali cattle waste. The total perception score reached 901, consisting of 448 for the odor sub-variable and 453 for the cleanliness sub-variable. This indicates that the community felt highly disturbed by the impact of livestock waste, particularly due to the strong, persistent odor and scattered cow dung in residential areas. The unpleasant odor was generated from the decomposition of organic materials in cattle feces and urine, which produced gases such as ammonia (NH3), methane (CH4), and hydrogen sulfide (H2S). Inadequate waste management also led to a decline in environmental cleanliness and an increase in fly populations. These findings confirm that improper management of Bali cattle farm waste has a significant negative impact on community comfort and environmental quality in the surrounding areas.